2015
DOI: 10.22230/ijepl.2015v10n5a572
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ moral agency and ethical decision-making: Towards transformational ethics

Abstract: This descriptive study provides a rich portrait of moral agency and ethical decision-making processes among a sample of Canadian school principals. Using an ethical responsibility framework linking moral agency and transformational leadership, the researchers found that 1) modeling moral agency is important for encouraging others to engage their own moral agency in the best interests of all children; 2) despite efforts to engage in collaborative decision-making, principals are often faced with the reality that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Transformational leadership has further been linked with the elements of morals and ethics (Cherkowski, Walker, & Kutsyuruba, 2015). In a study of school principals, Sagnak (2010) found that transformational leadership was a significant predictor of ethical school climate.…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%
“…Transformational leadership has further been linked with the elements of morals and ethics (Cherkowski, Walker, & Kutsyuruba, 2015). In a study of school principals, Sagnak (2010) found that transformational leadership was a significant predictor of ethical school climate.…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%
“…This finding is vital as McCabe (2013) states ethical relationship requires trust and integrity. Using an ethical leadership and decision-making approach helps administrators creating an ethical environment at school (Cherkowski, Walker, & Kutsyuruba, 2015;Gardiner & Tenuto, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…First, ethics of justice that covers the oldest philosophical theories focuses on rights, law, and democracy, and concepts such as equality, fairness, and freedom (Cherkowski et al, 2015; Shapiro & Stefkovich, 2016). According to Starratt (1994), the ethics of justice is rooted in two philosophical traditions: principled ethics and consequential ethics.…”
Section: Teaching Notesmentioning
confidence: 99%